SNEDDS to improve the bioactivities of Pandanus tectorius leaves: Optimization, antioxidant, and anticancer activities via apoptosis induction in human cervical cancer cell line - Alifa Husnun Kholieqoh, Murni Nur Islamiah Kassim, Tengku Sifzizul Tengku Muhammad, Khairul Anam, Yeong Yik Sung, Hermansyah Amir, Husna Nugraha Praja, Yosie Andriani (Journal of Applied Pharmaceutical Science, 2024)
Cancer continues to be a deadly disease on a global scale. Furthermore, despite the high expense of their development, synthetic chemotherapeutic drugs currently being used in clinical settings have failed to meet expectations during the past ten years. Therefore, new herbal medications might be alternative anticancer agents that are effective and affordable. Antioxidants in herbs might lessen oxidative stress and prevent carcinogenesis by slowing down and blocking the initiation of cancer cell development. Some researchers have reported that Pandanus tectorius has antioxidant activity. However, the antioxidant and anticancer properties of P. tectorius leave (PTL) in the form of self-nanoemulsifying drug delivery system (SNEDDS), specifically against human cervical cancer cells (HeLa) have not been studied. This study examined the anticancer activity of PTL-SNEDDS via induction of apoptosis on HeLa cells. All three PTL extracts (hexane, ethyl acetate, and methanol) were successfully formulated into SNEDDS formulation and showed improvement in antioxidant and anticancer activity compared to the crude extract. The cells’ morphological characteristics showed that PTL-SNEDDS-treated cells died from both early and late apoptosis. Thus, these findings introduce PTL-SNEDDS as an anticancer agent against human cervical cancer.
Keywords: SNEDDS, cervical cancer, apoptosis, coastal plant, oral bioavailability